LASER THERAPY IN THE TREATMENT OF ORAL MUCOSITIS IN ONCOLOGY PATIENTS - Ribeiro, Maria Cecilia Lima Pontual; Unifacol (2024)
The oral mucositis affects between 89% and 97% of the patients that are users of chemotherapy and radiotherapy as treatment for malignant neoplasms, presenting the potential to interfere directly in the patient's well-being. However, the use of low-power laser therapy has proven to be the most appropriate treatment for oral mucositis, acting through photophysical and biochemical processes that increase cellular metabolism, stimulating mitochondrial activity, acting as an analgesic, anti-inflammatory and repairing agent of the mucosal lesion. This study aims to analyze the efficacy of low intensity laser in the prevention and treatment of oral mucositis in patients exposed to radiotherapy and chemotherapy in the head and neck region. This is a descriptive/narrative literature review, in which the SciELO, LILACS, Pubmed and Medline databases were searched. The following descriptors were used: Oral mucositis; Laser therapy; Radiotherapy; Chemotherapy. The studies showed that in most patients who were prophylactically submitted to laser therapy sessions prior to the antineoplastic treatment, there was no development of lesions on the mucosa or when developed, the mucositis was mild, not altering the patient's well-being.